Is libertarianism the new future? Analyzing ideological and philosophical roots of the libertarian thought in the United States - Ягублу, Н. Н.; Yagublu, N. N. (Одеса : Видавничий дім «Гельветика», 2021)
Libertarianism as a political ideology and movement has garnered big curiosity in American political discourse in recent years. This support was further solidified with the achievement of getting the most votes ever in the history of the Libertarian Party, in 2016 U.S. presidential election. This research paper thoroughly examines the characteristics, main concepts and criticism of the ideology by continuously providing detailed outlook on the important libertarian notions and elaborating the discussed ideas through carefully-thought, case by case examples.The scientific work is multidimensional and multifaceted in its scope, and contains arguments with their counter-arguments to depict a broad, rational picture. Thus, the reader can see, fathom and compare the shortcomings and advantages of the talked ideas more effectively. Libertarian philosophy gives huge importance to the notions of liberty, freedom and individualism. Apart from this, another common thing that brings all libertarians together is their lack of trust to the government. Hence they always aspire to limit the role of it. Libertarians always emphasize the importance of free markets and vigorously express their discontent with any outside intervention to it, especially the one by the government. There are many different forms of libertarianism, some of them are more radical and support no-state structure. Libertarians, in principle, are not really concerned with inequality; they actually consider it positive to some extent.Although on the surface level the rationale behind many libertarian ideas seems reasonable and convincing, the empirical evidence and analyzing the results of actions which occur as the direct implementation of these principles show the necessity of a more comprehensive and accommodating approach. As society, economy and governing are so interconnected and intertwined with each other, certain actions have unintended consequences and in long term may yield destructive effect. The empirical reality should be taken into account in order to formulate effective policies for the benefit of the people.

Лібертаріанство як політична ідеологія і рух в останні роки викликає великий інтерес в американському політичному співтоваристві. Цей інтерес ще більше зміцнився з отриманням лібертаріанською партією на президентських виборах в США в 2016 році найбільшої кількості голосів у своїй історії. У цій статті докладно розглядаються характеристики, основні концепції лібертаріанства, дається критика ідеології, огляд основних лібертаріанському понять, аналіз обговорюваних ідей за допомогою ретельно продуманих конкретних прикладів. Це дослідження багатогранне і багатоаспектне за своєю структурою і містить докази і контрдокази, щоб зобразити широку реальну картину розвитку лібертаріанства. В результаті читач може більш ефективно побачити, зрозуміти і порівняти недоліки і переваги обговорюваних ідей. Філософія лібертаріанство надає виняткового значення поняттям свободи, волі й індивідуалізму. Крім цього, є ще одна спільна риса, яка об'єднує всіх лібертаріанців, – це відсутність довіри до уряду. Саме тому вони завжди прагнуть обмежити його роль. Лібертаріанці підкреслюють важливість вільного ринку і рішуче висловлюють своє невдоволення будь-яким втручанням у нього ззовні, особливо з боку уряду. Є безліч різних форм лібертаріанства, деякі з них більш радикальні і підтримують недержавні структури. Лібертаріанців насправді практично не хвилює нерівність, вони дійсно вважають це до певної міри позитивним. На поверхневому рівні логічне обґрунтування багатьох лібертаріанських ідей здається розумним і переконливим, проте емпіричні дані й аналіз результатів дій, які відбуваються при безпосередньому застосуванні цих принципів, показують необхідність всеосяжного і гнучкого підходу. Оскільки суспільство, економіка й управління тісно взаємопов'язані і переплетені між собою, певні дії тут можуть мати непередбачені наслідки і в довгостроковій перспективі виробляти руйнівний ефект. Щоби сформулювати ефективну політику в інтересах людей, слід брати до уваги соціальну реальність.

Либертарианство как политическая идеология и движение в последние годы вызывает большой интерес в американском политическом сообществе. Этот интерес еще больше укрепился с получением либертарианской партией на президентских выборах в США в 2016 году наибольшего количества голосов в своей истории. В этой статье подробно рассматриваются характеристики, основные концепции либертарианства, дается критика идеологии, обзор основных либертарианских понятий, анализ обсуждаемых идей с помощью тщательно продуманных конкретных примеров. Это исследование многогранное и многоаспектное по своей структуре и содержит доказательства и контрдоводы, чтобы изобразить широкую реальную картину развития либертарианства. В результате читатель может более эффективно увидеть, понять и сравнить недостатки и преимущества обсуждаемых идей. Философия либертарианство придает исключительное значение понятием свободы, свободы и индивидуализма. Кроме этого, есть еще одна общая черта, которая объединяет всех либертарианцев, - это отсутствие доверия к правительству. Именно поэтому они всегда стремятся ограничить его роль. Либертарианцы подчеркивают важность свободного рынка и решительно выражают свое недовольство любым вмешательством в него извне, особенно со стороны правительства. Есть множество различных форм либертарианства, некоторые из них более радикальные и поддерживают негосударственные структуры. Либертарианцев самом деле практически не волнует неравенство, они действительно считают это в определенной степени положительным. На поверхностном уровне логическое обоснование многих либертарианских идей кажется разумным и убедительным, однако эмпирические данные и анализ результатов действий, которые происходят при непосредственном применении этих принципов, показывают необходимость всеобъемлющего и гибкого подхода. Поскольку общество, экономика и управление тесно взаимосвязаны и переплетены между собой, определенные действия здесь могут иметь непредвиденные последствия и в долгосрочной перспективе производить разрушительный эффект. Чтобы сформулировать эффективную политику в интересах людей, следует принимать во внимание социальную реальность.
Yagublu N. N. Is libertarianism the new future? Analyzing ideological and philosophical roots of the libertarian thought in the United States / N. N. Yagublu // Актуальні проблеми політики : зб. наук. пр. / редкол.: С. В. Ківалов (голов. редкол.), Л. І. Кормич (голов. ред.), І. М. Милосердна (відп. ред.) [та ін.] ; НУ «ОЮА», Південноукр. центр гендер. проблем. – Одеса : Видавничий дім «Гельветика», 2021. – Вип. 67. – С. 125-134.
Keywords: libertarianism; ideology; free market; individualism; behavioral economics; лібертаріанство; ідеологія; вільний ринок; індивідуалізм; поведінкова економіка; либертарианство; идеология; свободный рынок; индивидуализм; поведенческая экономика; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Political science